PENGARUH MEDIA SOSIAL TERHADAP NILAI-NILAI MODERASI BERAGAMA DILINGKUNGAN MAHASISWA FEBI - Dwi Sintia Rahmawanti; Rossidah Rihadatul Aisi; Nailis Surooya; Ahmad Tubagus Surur (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to analyze the influence of social media in spreading the values ​​of religious moderation in the student environment. The writing method uses library research or literature reviews sourced from journals and e-books regarding the harmonization of science and religion. The data source comes from interviews with several samples of students from the Faculty of Economics and Islamic Business, UIN K.H Abdurrahman Wahid Pekalongan. The results of this research state that social media platforms such as Twitter, Instagram and Tiktok can provide a medium for discussion with fellow students or the wider community. If these various platforms are used for discussion properly, they can encourage them to think moderately, accept existing differences, and understand more deeply about religious moderation. Apart from that, they can also be influenced by public figures and influencers. There is a lot of content in the form of articles and videos that emphasize the importance of religious moderation.